Quasi-metal for highly sensitive and stable surface-enhanced Raman scattering - Tian, Zheng (2020)
Compared with the noble-metal surface-enhanced Raman scattering (SERS) substrates activated by the surface plasmon resonance (SPR)-induced electromagnetic mechanism (EM), the relative low sensitivity and stability of the chemical mechanism (CM)-based substrates are the biggest obstacles to their applications. Herein, we report that quasi-metallic VO2 nanosheet arrays can be used as a sensitive and stable SERS substrate. The lowest detectable limit of analyte adsorbed on the VO2 nanosheets achieves 10−10 M and the maximum Raman enhancement factor (EF) reaches 6.7 × 107, which is comparable with that of the noble metals. The experimental and theoretical results demonstrate that the SERS performance of the VO2 nanosheets comes from the strong interfacial interactions based on charge transfer and the vigorous SPR effects. Our research results demonstrate that quasi-metals are very promising SERS detection platforms and reveal that CM, like EM, contributes significantly to the SERS activity of quasi-metals.